Ibuism of Political Islam in the Election of Jakarta Governor in 2017 - Andriasanti, Lelly (Jurnal Perempuan, 2018)
The chaotic political issues always accompany the nation of Indonesia until this day. One of them is reflected in political dimension which summarized on the intolerance narrative in the election of Jakarta governor in 2017. Nonetheless, gender and women dimensions seem to shrink from public attention. Within the framework of the state, the important role of women for national life is reduced in the ideology of ibuism. This ideology actually finds a way in triggering activation of women when adapting to Political Islam. For that reason, research question of this paper is how the ibuism of political Islam affect the perception and preferences of female voters in the election of Jakarta governor in 2017? In order to answer the question, this paper uses a qualitative methodology with a phenomenological approach. As the final result, this paper conclude that in the framework of ibuism of political Islam, women played a role as agent which directing women voter perception. It is worked in taklim's mobilization network where women voter are asked vow to vote or do not vote particular candidate in Jakarta governor election in 2017.Â Â